Educational Nursing Intervention in Reducing Hospital Readmission and the Mortality of Patients with Heart Failure: A Systematic Review and Meta-Analysis - Cleidinaldo Ribeiro de Goes Marques; Andreia Freire de Menezes; Yasmim Anayr Costa Ferrari; Alan Santos Oliveira; Arthur César Melo Tavares; André Sales Barreto; Rita de Cássia Almeida Vieira; Cassiane Dezoti da Fonseca; Eduesley Santana-Santos (Journal of Cardiovascular Development and Disease, 2022)
(1) Background: Heart failure (HF) represents a public health problem due to its high morbidity and mortality, increased consumption of health resources, prolonged hospitalization, and frequent readmissions. This study was conducted to evaluate the effectiveness of a nursing educational intervention using home visits (HV) combined with telephone contact in reducing hospital readmission and the mortality of patients with HF. (2) Methods: This is systematic review and meta-analysis of randomized controlled trials (RCTs). The databases used were CINAHL, Cochrane, PubMed and SciELO. A gray literature search included Google Scholar, OpenThesis, Clinical trials and reference lists of eligible studies. RCTs of patients diagnosed with HF were included, distributed between the control group (CG) and intervention (IG), in which the IG was submitted to the nursing intervention with HV and telephone contact in association and analyzed the result of readmission and mortality. (3) Results: The search resulted in 2528 articles and, after following steps, 11 remained for final analysis. A total of 1417 patients were analyzed and distributed: 683 in the IG and 734 in the CG. As a primary outcome, the meta-analysis identified a 36% reduction in the risk of readmission [RR 0.64, 95% CI, 0.54–0.75, p < 0.01] and a 35% reduction in mortality in the IG [RR 0.65, 95% CI, 0.50–0.85, p < 0.01]. Heterogeneity was moderate for readmission and homogeneous for mortality. (4) Conclusions: HV and telephone contact are an effective intervention strategy for nurses’ educational practice.